2014
DOI: 10.1002/elsc.201400026
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive online biomass detector system for cultivation in shake flasks

Abstract: A novel online sensor system for noninvasive and continuous monitoring of cell growth in shake flasks is described. The measurement principle is based on turbidity measurement by detecting 180°‐scattered light and correlation to OD by nonlinear calibration models. The sensor system was integrated into a commercial shaking tablar to read out turbidity from below the shake flasks bottom. The system was evaluated with two model microorganisms, Escherichia coli K12 as prokaryotic and Saccharomyces cerevisiae as eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…In 2014 Scheper and Beutel et al proved its 9 biocompatibility and autoclavability for labware in use. Well plates and shake flask caps were 10printed and tested successfully with yeast cells and mammalian cells[24,25].…”
mentioning
confidence: 99%
“…In 2014 Scheper and Beutel et al proved its 9 biocompatibility and autoclavability for labware in use. Well plates and shake flask caps were 10printed and tested successfully with yeast cells and mammalian cells[24,25].…”
mentioning
confidence: 99%
“…Based on this idea, a novel online sensor system for noninvasive monitoring of biomass concentration by turbidity measurement in cultivation vessels has been developed [30]. Scattered light is measured through the vessel wall and correlated to optical density using nonlinear calibration models.…”
Section: Biomass Concentrationmentioning
confidence: 99%
“…Other advantages offered by working at the laboratory scale are the optically clear cultivation medium prepared from laboratory-grade chemicals and clean water, and the transparent reactor walls enabling noninvasive optical measurement with sensors fixed on the outside. Such sensors can be employed not only for reading of optical density and fluorescence [17], of scattered light [30], or for advanced sensors as Raman spectroscopy [31] but also for physicochemical variables as pH, pO 2 , and pCO 2 with fluorescing sensor spots attached inside the reactor or shake flask [30] and read out by fiber optics placed on the outside. Microalgae also have specific advantages for sensor development in contrast to other microorganisms: microalgal cells are larger than bacteria and contain specific pigments absorbing in the visual range but not in the infrared [32], contain organelles small enough for Mie light scattering in the visible (VIS) and near-infrared (NIR) range [33], and the principal pigment, chlorophyll a, can be used as a probe of photosynthetic activity thanks to its fluorescence properties [34].…”
mentioning
confidence: 99%
“…Several model microorganisms and cell lines representing aerobic and facultative anaerobic bacteria, fungi, yeasts and mammalian cells were chosen for the evaluation of the sensor. The technical design and the functional principle using an acceleration sensor have been described previously [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The focus lies on the evaluation of the biomass sensor based on backward light scattering. The application spectrum was expanded to four new organisms in addition to E. coli K12 and S. cerevisiae [ 1 ]. It could be shown that the sensor is appropriate for a wide range of standard microorganisms, e.g., L. zeae, K. pastoris, A. niger and CHO-K1.…”
mentioning
confidence: 99%